Coronavirus Vocabulary as a Communication “Tool” - Adilkhanyan, Anahit (Bulletin of Yerevan University B: Philology, 2023)
The article is dedicated to the impact of COVID – 19, which has plagued the word without precedent, on the vocabulary of the Armenian language. Due to created new situation, new words and phrases were created with the foreign word <<korona>>, borrowings from English were made, the meanings of the words in the vocabulary were expanded. We have classified this coronavirus vocabulary according to function, medical terms, words and phrases that have receved public, expressing stylistic nuances, also according to thematic groups, groups of people carrying the virus, the occupation of people related to the epidemic, the names of the code of conduct, the names of objects, the names of diseases related to the epidemic. This exam (about 122 words and phrases) proves that world events also have a great influence on the language, and reacts to them in its own way. The words created during the pandemic, idioms, as well as non-verbal means, convey information about a phenomation of social importance, which is necessary to orientate people and regulate their actions. And the words will go out of use over time, becoming historical words characterizing the coronavirus period of the 21st century and will be recorded in dictionaries, replenishing the vocabulary of the Armenian language.